2017
DOI: 10.1177/2192568217694144
|View full text |Cite
|
Sign up to set email alerts
|

Thirty-Day Readmission Risk Factors Following Single-Level Transforaminal Lumbar Interbody Fusion (TLIF) for 4992 Patients From the ACS-NSQIP Database

Abstract: Study Design:Retrospective cohort study.Objective:To describe the readmission rate and identify risk factors associated with 30-day readmission after transforaminal lumbar interbody fusion (TLIF) surgery.Methods:Patients who underwent elective single level TLIF surgery from 2011 to 2013 were identified in the American College of Surgeons National Surgical Quality Improvement Program (ACS-NSQIP) database. Emergency or trauma cases were excluded. Preoperative, intraoperative, and postoperative variables were ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 21 publications
(44 reference statements)
2
31
1
Order By: Relevance
“…The complication and readmission rates reported in the literature vary between studies. Studies on the National Surgical Quality Improvement Program (NSQIP) database found a 5.51% readmission rate within 30 days [47] and a 4% major complication rate [48], similar to Chan et al, who reported a 3.5% 3-month readmission rate [49]. These rates are relatively similar to the readmission rate calculated for the control group in the current study.…”
Section: Discussionsupporting
confidence: 89%
“…The complication and readmission rates reported in the literature vary between studies. Studies on the National Surgical Quality Improvement Program (NSQIP) database found a 5.51% readmission rate within 30 days [47] and a 4% major complication rate [48], similar to Chan et al, who reported a 3.5% 3-month readmission rate [49]. These rates are relatively similar to the readmission rate calculated for the control group in the current study.…”
Section: Discussionsupporting
confidence: 89%
“…In a similar study of the ACS-NSQIP, Garcia et al reviewed single-level TLIF surgery from 2011 to 2013 with the intent of evaluating 30-day re-admission risk factors [13]. This study did not stratify by patient discharge status.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 4992 patients who met inclusion criteria, 275 (5.5%) were re-admitted within 30 days of their index TLIF procedure and 179 (3.6%) required re-operation of their index TLIF procedure. Following the work by Garcia et al [13], Katz et al reported their review of the ACS-NSQIP database comparing anterior to posterior fusion approaches and the implications to 30-day outcomes [14]. PLIF and TLIF patients were grouped together into posterior fusion and ALIF with LLIF patients were grouped into anterior fusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study aims to investigate differences between patients who were discharged early and those who were not following lumbar fusion surgery, focusing on the rates of readmission and complications that required secondary surgery. Since the rates of success and patient satisfaction for common lumbar fusion surgery have become high in the past decades [16,17], the need for readmission or reoperation was low in each surgeon's or institute's series [18][19][20][21][22]. Therefore, there was rarely an adequate number of patients with high enough rates of follow-up for investigation of readmissions or reoperations in lumbar spinal fusion surgery.…”
Section: Introductionmentioning
confidence: 99%